Laryngopharyngeal reflux in the light of current medical knowledge – a literature review - Mieruszyńska, Stella; Mikołajczyk, Jagoda; Gołębski, Maciej; Nowak, Wojciech; Kukla, Zuzanna; Krzemińska, Paulina; Sawicki, Mirosław; Sadowska, Izabela; Włosiański, Jakub; Musialik, Sebastian (Journal of Education, Health and Sport, 2025)
Introduction and aim of the work: Laryngopharyngeal reflux often occurs in daily otolaryngological clinical practice. Diagnostics and treatment of this disease are complex for clinicians. Proton pump inhibitors cause many adverse effects, so alternative therapeutic methods are required. This study aims to submit current medical knowledge about laryngopharyngeal reflux, including possible treatment options. Materials and methods: The literature review of medical articles published between 2014 and 2024 was performed. These papers were accessed from the PubMed and Springer Nature Link databases. To find relevant articles, the following keywords were used: “laryngopharyngeal reflux”, “reflux laryngitis”, “proton pump inhibitors”, and “baclofen side effects”. State of knowledge: Symptoms of laryngopharyngeal reflux can result in reduced quality of life. Laryngopharyngeal symptoms are not that specific. Patients often search for a reason for their complaints at different specialists. Treatment of this disease is usually based on the trial-and-error method and observing patients’ responses. Summary: The accurate incidence of laryngopharyngeal reflux is not known. Various factors influence the occurrence of this disease. There are disparate opinions about using 24-hour pH monitoring as a gold standard; thus, other methods are sought. Proton pump inhibitors are the most common drugs used in the therapy, but their effectiveness is doubtful. More research should be done on the different methods of laryngopharyngeal reflux treatment. Pepsin inhibitors seem like an auspicious alternative, but there are too few studies on this subject.